Aphakic macular oedema following prosthetic lens implantation. Issue 5 (May 1977) - Easty, D.; Dallas, N.; O'Malley, R.
Abstract : Fluorescein angiography of the iris was performed on patients with plastic lens implants with cystoid oedema of the macula, and the nature of the vascular changes was compared with controls provided by patients who did not have macular disease. Densitometry was used to quantitate leakage of fluorescein dye into the anterior chamber in residual angiograms 5 minutes after injection. Cystoid oedema was associated with marked increase in vascular permeability of the iris in the patients with implants, and in aphakics without implants, but to a lesser degree. Although it cannot be concluded that implants themselves cause either the increase in permeability or the onset of macular oedema, the presence of such implants must be considered an additional hazard in an eye which is already at risk. Iris angiography can be used as a diagnostic aid in patients in whom macular oedema is suspected. A persistent increase in permeability associated with a reduction in visual acuity should act as a warning of further visual loss and of eventual cystoid macular degeneration.